2022
DOI: 10.1002/path.5890
|View full text |Cite
|
Sign up to set email alerts
|

Glomerulonephritis and autoimmune vasculitis are independent of P2RX7 but may depend on alternative inflammasome pathways

Abstract: P2RX7, an ionotropic receptor for extracellular adenosine triphosphate (ATP), is expressed on immune cells, including macrophages, monocytes, and dendritic cells and is upregulated on nonimmune cells following injury. P2RX7 plays a role in many biological processes, including production of proinflammatory cytokines such as interleukin (IL)‐1β via the canonical inflammasome pathway. P2RX7 has been shown to be important in inflammation and fibrosis and may also play a role in autoimmunity. We have developed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…In a model of renal fibrosis secondary to E. coli ‐induced pyelonephritis, we were able to show that P2X 7 R‐deficient mice were protected against renal fibrosis without interfering with the earlier stage of renal damage, inflammation and activation of tissue fibroblasts (Therkildsen et al., 2019). In support of the notion that P2X 7 Rs are not involved in early renal damage, it has been demonstrated that the lack of P2X 7 Rs did not influence the renal damage seen in models of glomerulonephritis and autoimmune vasculitis, including the activation of fibroblasts measured as increased α‐SMA expression (Prendecki et al., 2022). Moreover, various reports about the P2X 7 R in renal damage and fibrosis have been inconsistent (Goncalves et al., 2006; Luz et al., 2019; Xu et al., 2022), questioning the P2X 7 as a relevant target for interference against fibrosis.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In a model of renal fibrosis secondary to E. coli ‐induced pyelonephritis, we were able to show that P2X 7 R‐deficient mice were protected against renal fibrosis without interfering with the earlier stage of renal damage, inflammation and activation of tissue fibroblasts (Therkildsen et al., 2019). In support of the notion that P2X 7 Rs are not involved in early renal damage, it has been demonstrated that the lack of P2X 7 Rs did not influence the renal damage seen in models of glomerulonephritis and autoimmune vasculitis, including the activation of fibroblasts measured as increased α‐SMA expression (Prendecki et al., 2022). Moreover, various reports about the P2X 7 R in renal damage and fibrosis have been inconsistent (Goncalves et al., 2006; Luz et al., 2019; Xu et al., 2022), questioning the P2X 7 as a relevant target for interference against fibrosis.…”
Section: Discussionmentioning
confidence: 91%
“…This study was carried out in female mice because urinary tract infections are primarily a female‐associated condition. There have been deviating findings regarding the P2X 7 receptor in experimental models for more severe renal fibrosis (Goncalves et al., 2006; Prendecki et al., 2022; Therkildsen et al., 2019). Here, we use unilateral ureteral obstruction (UUO) to evaluate the effect of lacking the P2X 7 receptor and review the potential effect of gender on the overall response.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats with this deletion, compared to wild-type PCK rats, had impaired renal cyst development and ATP urinary release, with the latter corresponding to decreased amounts of renal pannexin-1 protein. Zinc finger nuclease technology has been used to globally delete the P2rx7 gene in Wistar Kyota rats, although the presence of escape variants in the brain could not be excluded [164]. This deletion did not protect rats from nephrotoxic nephritis, glomerulonephritis, or autoimmune nephritis, indicating P2X7 is not essential for the development of these disorders.…”
Section: P2rx7 Gene Knockout Rat Modelsmentioning
confidence: 99%